The Effect of A Proposed Training Program In volleyball On Some Physiological and Skill Variables - Azab, Mahmoud (Journal of Physical Education, 2017)
The Effect of A Proposed Training Program In volleyball On SomePhysiological and Skill VariablesThe study aimed to know the effect of the proposed training program involleyball on some physiological variables and skill,.The study was conducted on 16-09-2016 until 14-12-2016 on a sample of 22 students from the specialization of PhysicalEducation in Palestine Technical University - Khadouri students. After statistical analysis ofappropriate data study researcher concluded that there are significant differences in each ofthe weight measurement and the percentage of grease and some volleyball skills (transmitteraccuracy, and scroll up and scroll down, and on this it was concluded the researcher set ofrecommendations including the need to take advantage of the proposed training program tochange the weight and the proportion of grease.The need to take advantage of the proposedtraining program to make a positive change in some skills for volleyball (serving ,forearmpassing , overhead passing